Implementation Of Apriori Algorithm To Analyze Sales Data Of Goods At Izza Aquarium Shop - Febianda, Kanita; Asnawati, Asnawati; Yupianti, Yupianti (Jurnal Media Computer Science, 2025)
Toko Izza Aquarium is a business that sells animal feed and aquarium equipment. This research analyzes the sales data of Toko Izza Aquarium by applying the Apriori algorithm with the aim of providing data-based strategic recommendations to increase sales and customer satisfaction. This research is also expected to contribute in the field of sales data analysis in small and medium enterprises. The application of data mining to analyze the sales data of the Izza Aquarium Store is to provide information. The results of the analysis of Monthly sales data for the Izza Aquarium Store. Can be used as a parameter for inventory management at the Izza Aquarium Store and also provides information about the best-selling items at the Izza Aquarium Store. In analyzing sales data, the Apriori method is applied, so that the final result stage of the analysis passes the Apriori Method stage by meeting the Minimum Support and Minimum Confidence that has been determined. Based on the results of tests carried out on a data sample of 20 transactions in August 2024, the sales products that are most in demand by the public meet Minimum Support of 15% and Confidence 90% It turns out that Misster Puss Salmon and Chat Choice Green.